Pengaruh Pengetahuan, Keberanian Risiko, dan Pengendalian Diri terhadap Keputusan Investasi Nasabah dalam Perspektif Manajemen Bank - Elfan Adiel Prastino; Khairudin Mufid; Ida Ayu Nuh Kartini (CENDEKIA : Jurnal Penelitian dan Pengkajian Ilmiah, 2026)
Investment activities have increasingly become an important part of financial decision-making, particularly in the context of banking services that offer various investment instruments to customers. However, the rise in investment interest is not always accompanied by adequate understanding, which may lead to irrational decisions and potential financial risks. This study aims to examine how investment knowledge, risk tolerance, and locus of control influence customers’ investment decisions from a banking management perspective. This research applies a qualitative approach using a literature study method by reviewing relevant textbooks, academic journals, and previous studies related to investment behavior and banking management. The analysis is conducted by connecting key concepts such as investment decision-making processes, risk-return relationships, and individual behavioral factors that shape investment choices. The findings indicate that investment knowledge plays a fundamental role in shaping more informed and rational decisions. In addition, risk tolerance determines how individuals respond to uncertainty, while locus of control reflects the ability to manage and control personal financial behavior. These three factors are closely related and collectively influence how customers make investment decisions. From a banking management perspective, understanding these aspects is essential in developing effective financial education programs and improving investment services for customers. Therefore, this study is expected to provide theoretical insights into investment behavior within the banking sector and serve as a reference for enhancing customer-oriented investment strategies.